Ignition sebagai Inovasi Keramik Pada Brand Onix Pottery dengan Mitra UD. Tri Surya Keramik - Paramita, Ni Kadek Leony Widya; Wiyasa, I Nyoman Ngidep; Laba, I Nyoman; Putra, Rai Gede Wahyudi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze creative industry-based entrepreneurship development strategies by emphasizing the optimization of Social Media Marketing (SMM) in promoting ceramic craft products through the Onix Pottery brand. Within the context of the Independent Learning Campus (MBKM) program, this activity represents applied learning, requiring students not only to understand theory but also to initiate and build their own businesses. The research method used was descriptive qualitative, with data collection techniques including interviews, observation, literature review, visual documentation, and market research using Google Trends. UD. Tri Surya Keramik was selected as a partner due to its strong track record in the ceramics industry since 1994. Onix Pottery, as a start-up, carries the